Writing a Research paper in political science. a Practical Guide to inquiry, Structure and methods - BAGLIONE, Lisa A (Sage Publication, 2011)
Even students capable of writing excellent essays still find their first major political science research paper an intimidating experience. Crafting the right research question, finding good sources, properly summarizing them, operationalizing concepts and designing good tests for their hypotheses, presenting and analyzing quantitative as well as qualitative data are all tough-going without a great deal of guidance and encouragement. This writing guide breaks down the research paper into its constituent parts and shows students what they need to do at each stage to successfully complete components until the paper is finished. Even writing an introduction, coming up with effective headings and titles, presenting a conclusion, and the important steps of editing and revising are covered with class-tested advice and know-how.